Peran Pestisida Nabati dalam Pemeliharaan Tanaman Masyarakat di Kelurahan Panji, Kabupaten Kutai Kertanegara - Alamsyah; Ramadhandita, Jauzaa Lisgia; Azzahra, Marshanda; Armanda, Nona Ardelia; Dwiyanto, Rangga (Jurnal Abdita Naturafarm, 2025)
In Panji Village, Kutai Kartanegara Regency, East Kalimantan Province, the community actively grows Family Medicinal Plants (TOGA) and vegetables. However, they often face challenges such as pest and disease attacks that can damage crops. To overcome this problem, farmers often use chemical pesticides, although their use can have a negative impact on the environment and human health if excessive. As a more environmentally friendly alternative, plant-based pesticides can be a solution. The use of plant-based pesticides, which are made from ingredients such as shallots, garlic, galangal, turmeric, and aloe vera, is not widely known in the community. By counseling and making vegetable pesticides independently, it is hoped that this method can be an effective and sustainable solution in overcoming pest problems, while still maintaining the health of the environment and family.